Overexpression of CENPL mRNA potentially regulated by miR-340-3p predicts the prognosis of pancreatic cancer patients - Zhongyuan Cui; Ling Du; Jielong Wang; Zhongzhuan Li; Jiehong Xu; Shiyu Ou; Dongliang Li; Shasha Li; Hanfang Hu; Gang Chen; Zhixian Wu (BMC Cancer, 2022)
Abstract Background In our previous study it was found that CENPL was overexpressed in hepatocellular carcinoma and significantly predicted patient's prognosis. However, the expression and prognostic value of CENPL in other gastrointestinal tumors remain unknown. Therefore, we investigated the expression and prognostic value of CENPL in esophageal carcinoma (ESCA), stomach adenocarcinoma (STAD), pancreatic adenocarcinoma (PAAD), colon adenocarcinoma (COAD) and rectum adenocarcinoma (READ). Methods In this study, Oncomine, GEPIA, OncoLnc, TIMER, cBioPortal, miRWalk and ENCORI databases were used to analyze the level of CENPL mRNA, prognostic value and potential regulatory mechanism of CENPL mRNA in tumors. The CENPL expression and clinicopathological data regarding PAAD were from the UCSC Xena database and univariate and multivariate Cox regression analyses were performed using R (Version 3.6.3). Immunohistochemical staining was used to verify the expression of CENPL protein in clinical specimens. Cytoscape (Version: 3.7.2) was used to visualize microRNA (miRNA) that potentially regulates CENPL. Results Gene differential expression analysis showed that CENPL mRNA was significantly overexpressed in ESCA, STAD, PAAD, COAD and READ (p < 0.01). The overexpression of CENPL mRNA was significantly correlated with the poor prognosis of PAAD patients (p < 0.05). However, there was no significant correlation between the level of CENPL mRNA and the prognosis of ESCA, STAD, COAD and READ patients (p > 0.05). Univariate and multivariate Cox regression analyses suggested that CENPL was a prognostic risk factor for PAAD. The mutation rate of CENPL in PAAD was 2.2% (17/850). There was no significant correlation between the CENPL expression and the infiltration levels of immune cells in PAAD (|Cor|< 0.5). Immunohistochemical staining showed that CENPL was overexpressed in 42% (11/26) of PAAD specimens, which was significantly higher compared with that in the normal tissues. The expression of miR-340-3p and miR-484 in PAAD were significantly lower than in the normal tissues (p < 0.05) and PAAD patients with lower expression of miR-340-3p had poorer prognosis (p < 0.05). Conclusion CENPL potentially regulated by miR-340-3p, is overexpressed in PAAD and predicts patient’s prognosis, suggestive of a diagnostic and prognostic value in PAAD patients.